If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -4y = 3 Reorder the terms: -4y + 3z = 3 Solving -4y + 3z = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3z' to each side of the equation. -4y + 3z + -3z = 3 + -3z Combine like terms: 3z + -3z = 0 -4y + 0 = 3 + -3z -4y = 3 + -3z Divide each side by '-4'. y = -0.75 + 0.75z Simplifying y = -0.75 + 0.75z
| -7(6)(-1)= | | 35k=1925 | | 5x-57-2x=63 | | 4x^2-28-32=0 | | 18d^5+6d^4+9d^3= | | 3+4Inx=5 | | -7n-10=60 | | X+9=90 | | 2x+2y+z=11 | | 1-17x+37x=1 | | 19-11/-2 | | 5+2x=-20+5x | | 1/8=z^(6x) | | -14x-25-22=79 | | 14x-25-22=29 | | 18d^5+6d^49+d^3= | | -77=-40m-37m | | 1/3x1/3x1/3x1/3x1/3 | | t-23=78 | | -52+T=4 | | -9(1+7b)=15 | | w+17=19 | | 18x^2-46x-552=0 | | cos(53)=x/7 | | y+50=60 | | 4x+4y=3.5 | | 6y-4=3 | | 9x-3=-33 | | 4m+5n=5 | | 17x+30=-939 | | 2x=6-4x+2-2x | | y=-2E+05ln(x)+1E+06 |